The Effect of Compression Ratio on a Diesel Engine Fueled with a Mixture of Medium Sulfur High Speed Diesel and Ethanol - Atok Setiyawan; Arif Fadhlullah (JMES: The International Journal of Mechanical Engineering and Sciences, 2019)
Various design modifications made by transportation equipment companies aim to increase the efficiency of fuel consumption. One of them is by reducing the dIndonesia relies on the use of fossil fuels (conventional), particularly in the fields of industry, transportation, and power generation systems. Fossil fuels are not sustainable energy sources, so their availability is limited. To reduce dependence on fossil fuels and reduce the negative impact on the environment, it is necessary to conduct research on energy sources, especially renewable and environmentally friendly ones. Bioethanol is a form of renewable energy that can be produced from plants. So that the use of fossil fuels can be replaced by ethanol fuel, especially for spark-ignition engines (SIE). However, when used in compressed ignition engines (CIE), plant fuels or vegetable oils have weaknesses that affect CIE performance, such as cetane number, calorific value, etc. so that engineering related to the fuel and engine is needed. This study will examine the effect of changes in the compression ratio in CIE fueled by a mixture of Indonesia medium sulfur content of Diesel Fuel (commercially name: Dexlite), Ethanol, and Emulsifier Tween 80 on engine performance and emissions. The results showed that the 10% emulsifier was used in all fuel mixtures because the separation time was the longest. After determining the emulsifier level, the DEX70 (70% Dexlite - 30% Ethanol) and DEX 80 (80% Dexlite - 20% Ethanol) fuels were determined because they have the best characteristics for exhaust gas emission parameters. Then, by changing the compression ratio on the engine, there is a change in engine performance and emission parameters. For DEX80 and DEX70 with CR 17.9 have the maximum brake thermal efficiency (BTE) as much as 25.52% and 25.16% respectively at maximum load, higher than Dexlite with CR 17.9 in which BTE as much as around only 24%. Increasing compression ratio significantly decrease smoke opacity of exhaust gas. DEX80 with CR 17 and CR 16 experienced an increase in smoke opacity by (175.41%) and (3.11%) against DEX80 with CR 17.9. Meanwhile, DEX70 with CR 17 and CR 16 experienced an increase in smoke opacity by (17.01%) and (236.05%) against DEX80 CR 17.9.